In: Computer Science
Show that ππππ + πππ π + ππππ + β― + ππππ = π£(πππππ) for π > 1
Solution:
To show: log1 + log2 + log3 + .....+ logn = (nlogn) for n > 1
Explanation:
=>Let say f(n) = log1 + log2 + log3 + .....+ logn and g(n) = nlogn
Simplifying f(n):
=>f(n) = log1 + log2 + log3 + .....+ logn
Using log property loga + logb = logab
=>f(n) = log(1*2*3*4...*n)
We know that 1*2*3...*n = n!
=>f(n) = logn(n!)
=>f(n) = nlogn asymptotically
Proving using limits:
=>Limit(n -> ){f(n)/g(n)} = Limit(n ->
){nlogn/nlogn}
=>Limit(n -> ){f(n)/g(n)} = Limit(n ->
){1}
=>Limit(n -> ){f(n)/g(n)} = 1(constant)
=>As Limit(n -> ){f(n)/g(n)} = 1(constant) so f(n) and g(n) have equal growth rate hence we can write f(n) =
(g(n)) or log1 + log2 + log3 + .....+ logn =
(nlogn).